COVID-19-related anxiety and the role of social media among Canadian youth - Kim, Soyeon; Belfry, Kimberly D.; Crawford, Jennifer; MacDougall, Arlene; Kolla, Nathan J. (Frontiers in Psychiatry, 2023)
Background: Current literature indicates that safety measures, including lockdowns during the COVID-19 pandemic, severely disrupted our lifestyle, marked by increased screen time. The increased screen time is mostly associated with exacerbated physical and mental wellbeing. However, the studies that examine the relationship between specific types of screen time and COVID-19-related anxiety among youth are limited. Methods: We examined the usage of passive watching, social media, video games, and educational screen time and COVID-19-related anxiety at the 5-time points (Early-Spring 2021, Late-Spring 2021, Fall 2021, Winter 2022, and Spring 2022) among youth in Southern Ontario, Canada (N=117, mean age=16.82, male=22%, non-White=21%) and investigated the role of 4 types of screen time in COVID-19 related anxiety. Descriptive statistics were conducted to examine the binary relationships between demographic factors, screen time, and COVID-related anxiety. Also, partially adjusted and fully adjusted binary logistic regression analyses were conducted to examine the association between the types of screen time and COVID-19-related anxiety. Results: During the late Spring of 2021, when the provincial safety restrictions were most stringent, screen time was the highest among the 5 data collection time points. Further, adolescents experienced the highest COVID-19-related anxiety during this period. On the other hand, young adults experienced the highest COVID-19-related anxiety during Spring 2022. In a partially adjusted model (accounting for other types of screen time), engaging in 1-5 hours per day on social media increased the likelihood of experiencing COVID-19-related anxiety compared to those who spend less than 1 hour per day (OR=3.50, 95%CI=1.14-10.72, P<.05). Other types of screen time were not significantly associated with COVID-19-related anxiety. In a fully adjusted model (accounting for age, sex and ethnicity besides four types of screen time), 1-5 hours per day of social media remained significantly associated with COVID-19-related anxiety (OR=4.08, 95%CI=1.22-13.62, P<.05). Conclusion: Our findings suggest that COVID-19-related anxiety is associated with youth engagement in social media during the COVID-19 pandemic. Clinicians, parents, and educators should work collaboratively to provide developmentally appropriate approaches to reduce the negative social media impact on COVID-19-related anxiety and promote/foster resiliency in our community during the recovery period.